Economic benefits and importance of TAPI Project - Popalzai, Mohammad Zahoor (IJRDO Journal of History & Geography, 2019)
TAPI project is a leading and the biggest economic project in the region the construction of which is going to really useful and profitable to all of the member countries. This is a mutual project, the gas pipeline of Turkmenistan passes from Afghanistan to the southern Asian countries and all of the four countries are responsible for the construction and security of this project. Afghanistan will earn millions of dollars with the construction of this project and totally it would provide job opportunities to thousands of unemployed people in Afghanistan and as well as thousands of people would be recruited in the security sector of this project. In this project, the original exporter of gas is Turkmenistan. The construction of this project cause billions of dollars most of which is going to be paid by Turkmenistan and will enlarge its economic and business relations with the member countries of the project and as well as will have a special position in the global trade market and will earn a huge amount of income from the gas being exported to other countries. Turkmenistan is one of the most developed countries having a huge amount of industries. Throughout this gas pipeline, gas will be reached to the 4 four countries and the production process will become faster in the industrial system which will bring a positive in the economics of all four countries.